THE EFFECTIVENESS OF GUIDED INQUIRY LEARNING OF INTEGRATED SCIENCE TO IMPROVE STUDENT’S COMPETENCE - Usmeldi, Usmeldi; Amini, Risda; Suyatna, Agus (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2019)
Natural Science is one of the subjects in Junior High School (SMP). Preliminary survey shows that many (65%) of students who have not finished learning science. The subject matter of science is not yet integrated. Teacher centered learning. Therefore, it is carried out an integrated science learning based on guided inquiry. The study aims to determine the effectiveness of integrated IPA learning based on guided inquiry to improve the competence of learners. This research uses quasi experiment method with pretest-posttest group control design. The subjects of the study were students of eight grades at SMP Negeri 24 Padang. Data were collected using observation sheets, learning outcome test, skill assessment sheets, and attitude questionnaires. The result of the research indicates that the learning of integrated science based on guided inquiry is effectively to improve the student’s competence, based on: (1) Mastery learning of has been achieved by most (87.5%) students on knowledge competence, 96.9% on skills and 100% on attitude competence. (2) The improvement of student’s competency on experiment class including high category on knowledge domain, (3) Average competence of experiment class is higher than control class. (4) The effect of the implementation of integrated science based on guided inquiry to the student’s competence including large categories. (5) Student response to the implementation of learning is very good category.